Estudio de la significación de la inseguridad ambiental en dos casos en Córdoba (Sustainability in Debate, 2019)
In this article, we studied the significance of pollution in two conflicts articulated around the environmental issue: Pueblos Unidos and VUDAS- neighbors united in Defense of a Safe Environment in Córdoba, Argentina. Environmental suffering is not experienced in isolation, but within discursive contexts and power relations. These contexts give shape to the ways in which the affliction is lived and understood in each case. Based on the content analysis of twenty in-depth interviews, we conclude that in the analyzed conflicts, two opposing senses are constructed in relation to contamination: while in Pueblos Unidos, the danger of contamination diseases is relativized, in a context of absence of other opportunities to ensure life, in VUDAS, pollution is the main structuring of the struggle as they denounce its presence and the disease of the bodies.